Associations of childhood trauma and executive functioning in everyday life of those with subjective cognitive complaints. Issue 1 (2nd January 2023) - Lantrip, Crystal; Szabo, Yvette Z.; Pazienza, Shawneen; Benge, Jared
Abstract: Subjective cognitive complaints are a frequent patient-reported problem. Some adults with cognitive complaints present to the neuropsychology clinic without a diagnosable cognitive disorder but experience subjective daily executive dysfunction. It is well-established that trauma may impact executive function; however, the nuances of this relationship remain of interest. The present study descriptively reports associations between executive function and childhood trauma as well as lifetime trauma and current posttraumatic stress disorder (PTSD) symptoms. Participants were 48 adults referred to a neuropsychology clinic for evaluation without an identified neurocognitive disorder. Correlations between self-reported executive dysfunction, as assessed by the Behavior Rating Inventory of Executive Function-Adult (BRIEF-A), childhood trauma as measured by the Childhood Trauma Questionnaire and lifetime and current symptoms using the PTSD Diagnostic Scale for Diagnostic and Statistical Manual of Mental Disorders-5 were conducted. Correlations indicated that emotional neglect was associated with BRIEF-A indices and specific subscales including self-monitoring, shifting attention, task initiation, and planning/organization. Childhood emotional and sexual abuse and physical neglect and abuse, lifetime trauma and current PTSD symptoms were not associated with BRIEF-A indices. Though preliminary, these results highlight that in this population, history of childhood emotional neglect is particularly important when considering etiology of daily executive function complaints. Clinical implications and limitations are discussed.